Improving the quantity, quality and transparency of data used to derive radionuclide transfer parameters for animal products. 2. Cow milk. (February 2017) - Howard, B.J.; Wells, C.; Barnett, C.L.; Howard, D.C.
Abstract: Under the International Atomic Energy Agency (IAEA) MODARIA (Modelling and Data for Radiological Impact Assessments) Programme, there has been an initiative to improve the derivation, provenance and transparency of transfer parameter values for radionuclides from feed to animal products that are for human consumption. A description of the revised MODARIA 2016 cow milk dataset is described in this paper. As previously reported for the MODARIA goat milk dataset, quality control has led to the discounting of some references used in IAEA's Technical Report Series (TRS) report 472 (IAEA, 2010). The number of Concentration Ratio (CR) values has been considerably increased by (i) the inclusion of more literature from agricultural studies which particularly enhanced the stable isotope data of both CR and Fm and (ii) by estimating dry matter intake from assumed liveweight. In TRS 472, the data for cow milk were 714 transfer coefficient (Fm ) values and 254 CR values describing 31 elements and 26 elements respectively. In the MODARIA 2016 cow milk dataset, Fm and CR values are now reported for 43 elements based upon 825 data values for Fm and 824 for CR. The MODARIA 2016 cow milk dataset Fm values are within an order of magnitude of those reported in TRS 472. Slightly bigger changes are seen in the CR values, but the increase in size of the dataset creates greater confidence in them. Data gaps that still remain are identified for elements with isotopes relevant to radiation protection. Highlights: The derivation, transparency and provenance of animal product transfer parameter values has been improved. The second revision of these tables is reported for cow milk. The number of Concentration ratio (CR) values has been considerably increased.